The feasibility of anterior plate fixation in distal-third humeral shaft fractures: a retrospective case series - Kim, Ki-Tae; Kim, Seung Je; Shim, Jae Woo (Archives of Hand and Microsurgery, 2025)
Purpose: The surgical approaches and types of implants used for the fixation of distal-third humerus shaft fractures remain a matter of debate. We examined fracture patterns and evaluated the feasibility of plate fixation via an anterior approach.Methods: We conducted a retrospective study of 22 patients who underwent surgical treatment for distal-third humerus fractures from 2019 to 2023, with a minimum follow-up period of 6 months for all included patients. An anterolateral approach was used to perform open reduction and internal fixation. The minimum cortical width required for screw fixation at the most proximal part of the distal fragment was set at 10 mm. Results: The mean age of the patients was 38 years. Simple spiral and wedge fractures were predominant (86.3%). The distal fragment fracture line distribution was, on average, 30 mm (4–50 mm) to 101 mm (57–145 mm) from the coronoid fossa proximal margin. The mean distance sufficient to achieve bicortical purchase, engaging both the near and far cortices, was 61 mm (36–96 mm). An anterolateral approach was used in 18 patients based on computed tomography measurements of approximately 50 mm. An average of eight cortices were fixed in the distal fragment. All patients achieved bone union within 12 weeks without complications (mean, 12.69±2.43 weeks).Conclusion: Stable fixation was achieved with an anterior straight plate when 50 mm of the distal fragment was secured from the coronoid fossa’s proximal margin, with both cortices measuring at least 10 mm in width.